Analytic trends in mathematical physics - Abdul Rahman, Houssam M. A.; Sims, Robert, 1975-; Young, Amanda, 1986- (Contemporary mathematics (American Mathematical Society) ;, 2020)
This volume contains the proceedings of the Arizona School of Analysis and Mathematical Physics, held from March 5-9, 2018, at the University of Arizona, Tucson, Arizona. A main goal of this school was to introduce graduate students and postdocs to exciting topics of current research that are both influenced by physical intuition and require the use of cutting-edge mathematics. The articles in this volume reflect recent progress and innovative techniques developed within mathematical physics. Two works investigate spectral gaps of quantum spin systems. Specifically, Abdul-Rahman, Lemm, Lucia,